ปัจจัยที่มีผลกระทบต่อรายการคงค้างและกระแสเงินสดจากกิจกรรมดำเนินงานในการอธิบายราคาหลักทรัพย์ : กรณีศึกษาบริษัทจดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย - พัชรสุดา ปัญญาชื่นสกุลสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
To study the explanatory power of accrual items and cash flows from operating activities in explaining stock price, and to study the factors affecting accrual items and cash flows from operating activities in explaining stock price. The sample consists of listed companies in the Stock Exchange of Thailand, including 17 business sectors from 6 industry groups during the years 1999 to 2006. The results of this study show that cash flows from operating activities are more powerful than accrual items in explaining stock price. The study of factors affecting value-relevance shows that cash flows from operating activities of firms with high net income or net loss from operation, firms with high amount of assets, firms with high earnings growth rate, and firms with high transitory earnings have more incremental power to explain stock price than accrual items. This study suggests that investors take into account other accounting information especially cash flows from operating activities in assessing stock price.